2015
DOI: 10.5888/pcd12.150037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Family Income on the Relationship Between Parental Education and Sealant Prevalence, National Health and Nutrition Examination Survey, 2005–2010

Abstract: IntroductionWe examined the association between sealant prevalence and parental education for different levels of family income, controlling for other covariates.MethodsWe combined data from 2005–2006, 2007–2008, and 2009–2010 cycles of the National Health and Nutrition Examination Survey. The study sample was 7,090 participants aged 6 to 19 years. Explanatory variables, chosen on the basis of Andersen and Aday’s framework of health care utilization, were predisposing variables — child’s age, sex, race/ethnici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…In this study, we found a significant difference in sealant retention according to the mother's education level and household income. Similar past studies have reported that higher household income is associated with a higher sealant retention rate [26]. For beneficiaries, the mother's education level demonstrated statistical significance in both Models 1 and 2, in which the covariates were adjusted.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we found a significant difference in sealant retention according to the mother's education level and household income. Similar past studies have reported that higher household income is associated with a higher sealant retention rate [26]. For beneficiaries, the mother's education level demonstrated statistical significance in both Models 1 and 2, in which the covariates were adjusted.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we found a signi cant difference in sealant retention according to the mother's education level and household income. Similar past studies have reported that higher household income is associated with a higher sealant retention rate [26]. For bene ciaries, the mother's education level demonstrated statistical signi cance in both Models 1 and 2, in which the covariates were adjusted.…”
Section: Classificationsupporting
confidence: 80%
“…Studies indicate that low sealant prevalence is associated with low health literacy 40 or low parental education, a predictor of health literacy. 41 Policies aimed at increasing oral health literacy among low-income caregivers could increase the number of high-risk children receiving sealants. School staff and teachers, who can also influence children’s participation in sealant programs, may also be unaware of the benefits of sealants.…”
Section: Discussionmentioning
confidence: 99%